A desapropriação como instrumento de fomento a empreendimentos privados - Cammarosano, Márcio Alexandre G. F (2017)
The present work is a study about the possibility of use by the Public Administration of the expropriation institute as a tool for fomenting private enterprises. In the first chapter we discuss the reasons why the state should intervene in the economic order, and how this duty is disciplined by the Federal Constitution of 1988. In the second chapter we investigate the principle of subsidiarity, in its vertical and horizontal aspects, understanding this principle as the delineating element of the roles of the State and society in the search for a fair and egalitarian distribution of social welfare. The third chapter is devoted to the study of state fomenting activity, from its first scientific systematization, including the analysis of the active and passive subjects, of the applicable norms, as well as the means allowed by the law. In the fourth and last chapter we analyze the expropriation institute and the possibility of its use as a tool to foment private enterprises, as well as the limits and indispensable procedures of this practice